2022-RA-1289-ESGO Understanding clinical and pathological heterogeneity of endometrial cancer with no specific molecular profile (NSMP). (20th October 2022) - de Vitis, Luigi Antonio; Schivardi, Gabriella; Fumagalli, Caterina; Zambetti, Benedetta; Ghioni, Mariacristina; Raviele, Paola Rafaniello; Rappa, Alessandra; Achilarre, Maria Teresa; Aloisi, Alessia; Garbi, Annalisa; Lapresa, Mariateresa; Parma, Gabriella; et al.
Abstract : Introduction/Background: No-specific molecular profile (NSMP) endometrial cancers (ECs) lack a unique molecular feature and show considerable molecular heterogeneity. However, CTNNB1 hotspot mutations have been associated with adverse outcomes. The aim of the study is to explore molecular features of NSMP-ECs and to investigate the role of CTNNB1. Methodology: Among all ECs undergoing molecular analysis at the European Institute of Oncology, Milan, between April 2019 and December 2021, NSMP-ECs were identified. The molecular profiling included MMR-proteins and p53 immunohistochemistry, microsatellite instability evaluation and Next Generation Sequencing of 26 cancer-related genes, including POLE, TP53 and CTNNB1. NSMP-ECs were classified according to CTNNB1 status. Clinicopathological characteristics between CTNNB1-mutated and CTNNB1-wild-type ECs were compared. To compare continuous and categorical variables Mann-Whitney test and chi-square test were used, respectively. Results: Overall, 124 (44.6%) NSMP-ECs were identified among the 278 ECs that underwent complete molecular analysis. Clinicopathological and molecular characteristics of NSMP-ECs are shown in figure 1 . The majority of NSMP-ECs were endometrioid (n=121, 97.6%), low-grade (n=107, 86.3%), FIGO stage I (n=82, 66.1%), with no/focal lymphovascular space invasion (n=119, 96.0%) and with <50% myometrial invasion (n=85, 68.5%). According to the ESGO/ESTRO/ESP guidelines, 52.4% (n=65) were low-risk ECs.The most commonly mutated genes were PTEN (n=82, 66%), CTNNB1 (n=48, 39%), PIK3CA (n=39, 31%) and KRAS (n=27, 22%). CTNNB1 and KRAS mutations were mutually exclusive (p<0.001).CTNNB1-mutated were younger (55.3±12.9 vs 63.2±12.3, p=0.002) than CTNNB1 wild-type. Histotype, myometrial invasion, lymphovascular space invasion, grade, stage, and ESGO/ESTRO/ESP risk class did not differ between the two groups ( table 1 ). Conclusion: Our study confirms the high prevalence of PI3K/AKT/mTOR and Wnt pathways alterations in NSMP-ECs and the mutually exclusive pattern between CTNNB1 and KRAS. Mutations in CTNNB1 occur in younger patients, but do not imply different clinicopathological characteristics.